A study on morbidity status of geriatric population in the field practice area of Karpaga Vinayaga Institute of Medical Sciences, Tamil Nadu, India - H., Gladius Jennifer; Lakshmi, P. A. Archana; D. C., Vidya; Das, Bagavan (International Journal Of Community Medicine And Public Health, 2016)
Background: Aging is a process of deterioration in the individual’s functional capacity that results from structural changes as age advances. India has acquired the label of “an aging nation” with 7.7% of its population being more than 60 years old. Research on geriatric morbidity and related risk factors are required to improve the delivery of health care to the elderly. This study was an attempt to study the morbidity status of geriatric people that may serve as a baseline data and also help in planning the health services. The aim of the study was to find the morbidity pattern among geriatric population in field practice area of Karpaga Vinayaga Institute of Medical Sciences, Kancheepuram, Tamilnadu, India. Methods: An observational study conducted in field practice area of Karpaga Vinayaga Institute of Medical Sciences, Tamilnadu, India from March 2016 to April 2016. Study participant who aged above 60 years were administered by pre tested, semi structured questionnaire after obtained informed consent. Descriptive statistics were calculated by using SPSS 18V. Results: Among 72 study participants, most common morbidity were arthritis (75%), followed by hypertension (63.9%), cataract (55.6%), low back pain and other pain (52.8%), diabetes (33.3%). 61% of study subjects reported more than one illness. Conclusions: There is high morbidity rate identified in this present study, there is an urgent need to develop geriatric health care services at primary health centre level.